ANALYSIS OF EFFECTIVENESS AND FACTOR OF INHIBITING THE IMPLEMENTATION OF ACTIVE TAX COLLECTION TO DISBURSEMENT OF TAX ARREARS (Case Study in KPP Pratama Malang Utara) - Wibowo, Yoga Mukti; Pusposari, Devi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims to find out the effectiveness of active tax collection in KPP Pratama Malang Utara. In addition, the objectives are to determine the limiting factor in the active tax collection in KPP Pratama Malang Utara. The method of study is qualitative descriptive approach. This study uses primary and secondary data. The result of study indicate that the active tax collection rate is still not effective. Results are not effective because there are factors of inhibiting the implementation of active tax collection. From interviews with the tax authorities found factors that cause of the implementation of tax collection are still weaknes from active tax collection process and low of public awareness in paying the tax. Â Keyword : Effectiveness, Tax Collection, Tax Arrears